Akhlak Santri Terhadap Guru di Pesantren Darul Arafah Raya Desa Lau Bakeri Deli Serdang Sumatera Utara - M. Farhan Roshan; Muhammad Muhammad (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
In the history of the relationship between teachers and students in the Islamic world, it turns out that little by little it has begun to change, moral values little by little have begun to diminish. As time goes by, not a few Islamic boarding schools try to adapt and are willing to accept changes, but there are also quite a few Islamic boarding schools that have the attitude of closing themselves off from all changes and influences of the times, and tend to maintain what they believe in. Likewise what happened at the Darularafah Raya Islamic Boarding School, Lau Bakeri Village, Deli Serdang, North Sumatra. Departing from the background of this problem, the authors formulated two problem formulations, namely what is the role of the ustadz or teacher in instilling moral education for students at the Darularafah Raya Islamic Boarding School? And what is the impact on students in improving moral education at the Darularafah Raya Islamic Boarding School? The methodology used in this research is field research (Field Research) with direct observation, interviews in the field with several ustadz and students. The results of research on the morals of santri towards ustadz at the Darularafah Raya Islamic boarding school are that there are several forms of moral development for santri, such as: First, the forms of moral formation in Islamic boarding schools include: moral education because students will automatically carry out these activities without having to be forced. Second, the role of the Ustadz in developing the morals of students in Islamic boarding schools includes: a) The Ustadz as a caregiver provides lessons in understanding, deepening, appreciating and practicing the teachings of the Islamic religion by emphasizing the importance of religious morals as a guide to daily behavior, b) The Ustadz as a teacher or lecturer and mentor for students. Guidance by providing appropriate advice explained in the Koran, hadith and books, c) Ustadz as a second parent for the students. Instilling faith in students, guiding religious practices and developing students' morals. And third, the impact of moral development on students in Islamic boarding schools includes: a) The impact of moral development on students provides positive values, b) the attitudes and behavior of the majority of students carry out all the rules in Islamic boarding schools, c) the morals of these students have a very good impact on assistance from guidance provided by ustadz and ustadzah as well as assistance from existing regulations.